ANALISIS IKLAN LAYANAN MASYARAKAT BERBASIS DIGITAL DALAM MEMBANGUN PEMAHAMAN MASYARAKAT TENTANG KEJAHATAN HOAKS - gesnida yunita (UNIVERSITAS NUSA PUTRA, 2023)
This study aims to analyze the effectiveness of digital-based public service advertisements in building public understanding of hoax crimes. Hoax crimes have become an increasingly worrying issue in today's digital era, where false information can quickly spread and affect people's perceptions and actions. Public service advertisements have the potential to become important tools in efforts to combat the spread of hoax crimes by providing accurate and educative information. This study uses a qualitative approach with content analysis methods to explore the meaning and messages contained in public service advertisements related to hoax crimes. Data is collected through searches of public service advertisements on digital platforms, such as social media, government websites and video sharing channels. The selected advertisements are then analyzed to identify communication strategies, core messages, and approaches used to build public understanding of hoax crimes. The results of the analysis show variations in the communication strategies used in public service advertisements. Some advertisements focus on providing factual information about hoax crimes and their negative impacts, while others place more emphasis on using emotional narratives to arouse feelings of concern and the need to be careful in sharing information. The core messages in advertisements tend to highlight the importance of verifying information before trusting and disseminating information, as well as inviting the public to actively participate in fighting hoax crimes. The conclusion of this study is that digital-based public service advertisements can be effective in building public understanding of hoax crimes by providing clear, accurate and relevant information.